Umphred's Neurological rehabilitation - Rolando T. Lazaro; Sandra Reina-Guerra; Myla Quiben; Darcy Ann Umphred (St. Louis : Mosby, 2020)
"Develop problem-solving strategies for individualized, effective neurologic care! Under the new leadership of Rolando Lazaro, Umphred's Neurological Rehabilitation, 7th Edition, covers the therapeutic management of people with activity limitations, participation restrictions, and quality of life issues following a neurological event. This comprehensive reference reviews basic theory and addresses the best evidence for evaluation tools and interventions commonly used in today's clinical practice. It applies a time-tested, evidence-based approach to neurological rehabilitation that is perfect for both the classroom and the clinic. Now fully searchable with additional case studies through Student Consult, this edition includes updated chapters and the latest advances in neuroscience."--Provided by publisher
Keywords: Internet Resources; Nervous system Diseases Physical therapy; Nervous system Diseases Patients Rehabilitation